Predictors of patient and system delay for primary percutaneous coronary intervention. (14th October 2021) - Candjondjo, A; Ferreira, J; Esteves, A; Farinha, J; Fonseca, M; Coelho, R; Gama, L; Sa, C; Lopes, A; Fernandes, A; Perdigao, A; Seixo, F; et al.
Abstract: Background: The delay times of the patient and the system for primary percutaneous coronary intervention (p-PCI) have a determining impact on the prognosis of patients with acute myocardial infarction with ST segment elevation (STEMI). Purpose: To identify the predictors of patient and system delay for p-PCI in the period of 2020 at a reference hospital for p-PCI. Methods: Patients submitted to p-PCI in the period from March to September 2020 were included and compared with the same period in 2019. We analyzed the differences between the two groups regarding the patient's delay times, time from the onset of symptoms to the first medical contact (FCM) and the system (time from the first contact with the health system to p-ICP). Data collection of the patient's previous history, coronary intervention performed and post-PCI follow-up was performed using the electronic patient record. Univariate analysis and logistic regression models from multivariate analysis were used to determine the predictors of "patient delay" and "system delay" and adjusted for confounding factors. The analysis was performed with a significance level of 5%. Results: We included in the study 255 patients who underwent p-PCI, of which 122 in the period from 2020 and 133 in the period from 2019. Regarding the characteristics of the population, there were no significant differences between the two periods. Regarding the patient's delay time, there were no statistically significant differences. The variable first medical contact with a non p-PCI center was the only variable associated with system delay>90 minutes in the multivariate analysis, OR (6.18: 95% CI, 1.91–20), p=0.002. There was a statistically significant association between the period of 2020 (pandemic period) and total ischemia time, but with a negative effect, dependent variable adjusted for confounding factors [adjusted OR: −0.10; 95% CI: −107.61 to −5.57; p=0.03]. Conclusion: In this study, the patient's admission to a non p-PCI centers was identified as the only predictor of longer delay until p-PCI (system delay). However, these results should serve as a contribution to decision making in order to mitigate risks, regardless of any associated catastrophe and eventually alert the population not to neglect the symptoms suspected of acute myocardial infarction. FUNDunding Acknowledgement: Type of funding sources: None.